Promoción turística por medio de las redes sociales y la afluencia de visitantes al Complejo San Francisco del cantón Buena Fé - Aviles Baque, Cinthia Daniela (2020)
This case study is aimed, at the tourist promotion that given to the San Francisco Complex located in the Buena Fé Canton this is one of the few tourist destinations that have a natural resource within the Canton with a unique singularity but the growth of the tourism business has not maximized, and the number of visitors is unstable. Faced with this phenomenon, he has been interested in studying tourism promotion through social networks to increase the number of visitors to the destination. Currently, the use of social networks provides many benefits and advantages in the field of tourism, allowing the information, communication, and promotion of the different trips of a destination to be easily disseminated. The types of research used was descriptive research and bibliographic documentary research. The results were obtained through research techniques, which were the survey and the interview, the method used was convenience sampling due to the emergency we are experiencing. The survey was applied to 125 people from the Buena Fé Canton, between 15 and 37 years of age, which allowed specifying which social networks are and the use they are given to promote the complex. The interview was conducted with a professional person on the subject considering the necessary measures that can be applied to increase the influx of visitors. After the analysis, it was concluded that the local population agrees with the tourist development in the complex. Although, that previously has not occurred. For this reason, it is essential to improve tourism promotion through social networks to publicize the site and help comprehensively in contributing to the influx of visitors.